A cupronickel-based micromesh film for use as a high-performance and low-voltage transparent heater1. Issue 32 (28th August 2015) - Kim, Han-Jung; Kim, Yoonkap; Jeong, Jun-Ho; Choi, Jun-Hyuk; Lee, Jihye; Choi, Dae-Geun
<x xml:space="preserve">Abstract</x> Uniformly interconnected CuNi mesh film was prepared by using a simple transfer printing method. The CuNi mesh films showed excellent heating performances, which reached a maximum steady-state temperature of 225 °C in 60 s, with respect to applied low-voltage (9 V), and better thermal stability than that of the pure Cu mesh film.